Perbandingan Kualitas Audit Perbankan Syariah di Malaysia dan Indonesia - Zakiyyatun Naqiah (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2022)
Abstract - This study aims to compare audit quality in Islamic banking in Indonesia and Malaysia by using Audit Quality Indicators (AQIF), such as Good Corporate Governance which increases the size of the board, sharia supervisory board, audit commiteee, frequency of audit meeting, audit tenure, auditor industry specialization and audit firm reputation used to obtain audit quality in sharia banking during the 2014-2017 period. The sample in this study used Purposive Sampling and obtained a sample of 12 Islamic banks in Indonesia and 11 Islamic banks in Malaysia. The data used is secondary data from financial or annual reports issued through the official website of Islamic banks. In comparing these two banks, the analysis used is a different test from the Independent Sample t-test. The results showed significant differences with a significance level of 0,000 on the size of the board, sharia supervisory board, audit tenure, auditor of industry specialization and audit firm reputation And there is no significant difference in the size of the audit committee with a significance level of 0.513, the frequency of the audit board with a significance level of 0.090, the audit tenure with a significance level of 0.124.